2022
DOI: 10.4102/ajod.v11i0.930
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of caregivers providing care to children with disabilities at non-governmental organisations in Tshwane townships, South Africa

Abstract: Background: Caregivers of children with disabilities are vital stakeholders when it comes to safeguarding the health, well-being and overall survival of the children that they care for. Caregivers, however, face many challenging conditions that make it difficult for them to optimally fulfil their caregiving role. Understanding these challenges is crucial for developing empowerment programmes for caregivers, which will ensure that children with disabilities receive comprehensive, optimal care and that caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, even though the status is formally regulated, it does not serve a function like a regular job or career (Wondemu et al 2022). One of the problems for caregivers is also the lack of public recognition and the perception that they are undervalued by the community, which leads them to isolate themselves (Akintola 2010;Moosa-Tayob and Risenga 2022). This lack of public recognition and undermining by the community could be characteristic of both the formal caregivers and the unemployed parents in our study.…”
Section: Discussionmentioning
confidence: 84%
“…However, even though the status is formally regulated, it does not serve a function like a regular job or career (Wondemu et al 2022). One of the problems for caregivers is also the lack of public recognition and the perception that they are undervalued by the community, which leads them to isolate themselves (Akintola 2010;Moosa-Tayob and Risenga 2022). This lack of public recognition and undermining by the community could be characteristic of both the formal caregivers and the unemployed parents in our study.…”
Section: Discussionmentioning
confidence: 84%
“…The parents of children with disabilities also continue to experience many challenging conditions that make it difficult for them to optimally fulfil their caregiving role and might face more lack of support, stress, and lack of coping compared to their counterparts, as reported in South Africa [76]. Additionally, researchers [77] reported that a lack of resources poses a further challenge to providing proper care to disabled young people in Malawi.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Caregiver's responses to this unusual situation are in uenced by various features, including both their genetic and acquired characteristics. [17] These responses can have signi cant impacts on the caregiver's health, well-being, and overall quality of life. [18] Different families may utilize different coping strategies to deal with these challenging situations.…”
Section: Introductionmentioning
confidence: 99%